2011
DOI: 10.18848/1832-2077/cgp/v07i01/54875
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Partnership for Education for Sustainability: New Zealand Vocational Education

Abstract: This year marks the midpoint of the Decade of Education for Sustainable Development but sustainability still remains a foreign concept in the New Zealand vocational and trade education curriculum. Thus research was conducted to gauge the existing perceptions of academics and industry and discover the reasons for the slow embedding of sustainability concepts in the curriculum. The research followed a qualitative research methodology using a case study as the method of inquiry which collected data through 8 in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Research undertaken in New Zealand [15] indicated that there were fundamental differences in opinion about the role of education for sustainability between students on one hand and their lecturers and industry personnel on the other. Students felt optimistic about the opportunities offered by sustainability whereas the latter saw little relevance for it.…”
Section: International Journal Of Information and Educationmentioning
confidence: 99%
“…Research undertaken in New Zealand [15] indicated that there were fundamental differences in opinion about the role of education for sustainability between students on one hand and their lecturers and industry personnel on the other. Students felt optimistic about the opportunities offered by sustainability whereas the latter saw little relevance for it.…”
Section: International Journal Of Information and Educationmentioning
confidence: 99%